Analysis of Perceptual Differences Between Employees and Management in Organizational Communication Practices at The Level of Culture in The Bucketlist Indonesia - Insani, Belariska Hidayah; Prasetyo, Bambang Dwi (Dinasti Research, 2024)
This study analyzes the perceptual differences between employees and management in organizational communication practices at The Bucketlist Indonesia, a family business operating in the tourism sector. Using a mini-ethnography approach and an interpretive paradigm, this study explores verbal and non-verbal communication applied within the context of organizational culture, utilizing Schein's (2004) level of culture theory. The findings reveal perceptual alignment in several aspects such as the logo and office layout, but also identify significant differences related to uniforms, appearance, and language style. These perceptual differences reflect variations in understanding and internalization of organizational values, which can impact service consistency and customer perceptions. This study highlights the importance of effective internal communication in creating a unified vision and improving service quality. The findings are expected to provide insights for The Bucketlist Indonesia and similar businesses in managing organizational communication to support growth and business success.